IV INTERNATIONAL BROCCOLI CONSUMPTION CONFERENCE «BROCCOLI. THE TASTE OF NATURE» - O. Frolova; M. M. Tareeva (Овощи России)
The IV International Broccoli consumption conference «Broccoli. The taste of nature» was hold on 7 and 8 October 2014 in the hotel NARVIL Conference & Spa in Serotsk (Poland) with the support of Sakata. The event was dedicated to the production, marketing, consumption and useful properties of broccoli.